Non-equilibrium dynamics of bulk-deterministic cellular automata - Wilkinson, Joseph W P (2022)
In this thesis we study simple one-dimensional nonequilibirum many-body systems, namely, reversible cellular automata (RCA). These are discrete time lattice models exhibiting emergent collective excitations---solitons---that move with fixed velocities and that interact via pairwise scattering. In particular, we study the attractively interacting Rule 201 RCA and noninteracting Rule 150 RCA which, together with the extensively studied repulsively interacting Rule 54 RCA constitute arguably the simplest one-dimensional microscopic physical models of strongly interacting and asymptotically freely propagating particles, to investigate interacting nonequilibrium many-body dynamics.